The alignment of Earthquake T-Axes with the principal axes of geodetic strain in the Aegean region - England, P (2003)
The relation between the orientations of the T-axes of earthquakes occurring within the continental crust of the Aegean, and the orientations of the principal axes of geodetic strains is examined. It is shown that the T-axes align with the principal horizontal extension axes to a degree that is unlikely to have arisen by chance, and it is concluded that the seismic deformation of the region is consistent with the response of a quasi-continuous medium to a stress regime that is organised on a regional scale.